Improved lithium-ion battery anode capacity with a network of easily fabricated spindle-like carbon nanofibers - Liu, Mengting; Xie, Wenhe; Gu, Lili; Qin, Tianfeng; Hou, Xiaoyi; He, Deyan (Beilstein Journal of Nanotechnology, 2016)
A novel network of spindle-like carbon nanofibers was fabricated via a simplified synthesis involving electrospinning followed by preoxidation in air and postcarbonization in Ar. Not only was the as-obtained carbon network comprised of beads of spindle-like nanofibers but the cubic MnO phase and N elements were successfully anchored into the amorphous carbon matrix. When directly used as a binder-free anode for lithium-ion batteries, the network showed excellent electrochemical performance with high capacity, good rate capacity and reliable cycling stability. Under a current density of 0.2 A g−1, it delivered a high reversible capacity of 875.5 mAh g−1 after 200 cycles and 1005.5 mAh g−1 after 250 cycles with a significant coulombic efficiency of 99.5%.
Keywords: carbon nanofiber network; electrospinning; lithium-ion battery; manganese oxide; nitrogen modification